Pengembangan Lembar Kerja Peserta Didik Berbasis Pendekatan Saintifik pada Tema 3 Benda Disekitarku Kelas III SD Swasta Nurhasanah Garu 1 - Emi Fauziah Siregar; Beta Rapita Silalahi (LP3M KH Yazid Karimullah Institute, 2024)
This research aims to produce products in the form of LKPD (Student Worksheets) Based on a Scientific Approach on Theme 3 Objects Around Me grade III SD Nurhasanah Garu 1 No.28 Kec. Medan Sandpaper and Knowing the feasibility level of developing LKPD Based on a Scientific Approach on Theme 3 Objects Around Me Class III SD Swasta Nurhasanah Garu 1 No.28 Kec. Medan Amplas. The type of research used is a type of research and development or Research and Development (R & D), this research and development method is a research method used to produce certain products and test the effectiveness of these products. Based on the results of research and development that has been carried out by researchers, it can be concluded that research and development uses stages with the ADDIE model , but researchers only reach the stage The development has produced products in the form of LKPD Media in thematic learning in elementary schools with the theme Objects Around Me. Based on the feasibility of the media from the input of experts, namely lecturers and teachers, media experts, namely lecturers. From the validation data from material experts (lecturers) reached 94%, learning experts (teachers) reached 95%. If the percentage obtained reaches 81% to 100%, then LKPD media is categorized as very feasible. From the calculation above , the percentage of 94% and 95% is obtained, so LKPD media is categorized as very feasible. Media experts reach 81%, so LKPD media is categorized as very good / very feasible. So the development of LKPD theme 3 objects around me grade III elementary school developed by researchers is stated to be very feasible to be used as a medium in the learning process.